10th International Symposium on High-Temperature Metallurgical Processing - Jiang, Tao (Metallurgist); Hwang, Jiann-Yang; Gregurek, Dean; Peng, Zhiwei; Downey, Jerome P.; Zhao, Baojun; Yücel, Onuralp; Keskinkilic, Ender; Padilla, Rafael (Minerals, Metals & Materials Series,, 2019)
In recent years, global metallurgical industries have experienced fast and prosperous growth. High-temperature metallurgical technology is the backbone to support the technical, environmental, and economical needs for this growth. This collection features contributions covering the advancements and developments of new high-temperature metallurgical technologies and their applications to the areas of processing of minerals; extraction of metals; preparation of refractory and ceramic materials; sintering and synthesis of fine particles; treatment and recycling of slag and wastes; and saving of energy and protection of environment. The volume will have a broad impact on the academics and professionals serving the metallurgical industries around the world.